Teotihuacan and Early Classic Mesoamerica: multiscalar perspectives on power, identity, and interregional relations - García-Des Lauriers, Claudia, editor; Murakami, Tatsuya, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2021)
The Early Classic period in Mesoamerica has been characterized by the appearance of Teotihuacan related material. Known for monumental architecture and dense settlement, became an urban center around 150 BC eventually dominating much of the Basin of Mexico and beyond until collapse. Explores the complex nature of Teotihuacan's interactions with other regions.--Provided by publisher.
Introduction: Teotihuacan and Early Classic Mesoamerica / Tatsuya Murakami and Claudia García-Des Lauriers -- Political dynamics and non-local resources at Teotihuacan: Early Classic interaction viewed from the metropolis / Tatsuya Murakami -- Interaction, ethnicity and subsistence strategies among the minority groups of the ancient city of Teotihuacan / Sergio Gómez-Chávez and Julie Gazzola -- Beyond the city: a regional perspective on Teotihuacan's growth in the Basin of Mexico / Sarah C. Clayton -- Creolization and ethnogenesis in Teotihuacan's hinterland: ZapoTeotihuacanos at El Tesoro, southern Hidalgo / Haley Holt Mehta -- The Cholula-Teotihuacan relation revisited / Patricia Plunket and Gabriela Uruñuela -- Identity, material culture and Teotihuacan hegemony in the Toluca Valley / Yoko Sugiura, Carmen Pérez, and Gustavo Jaimes Vences -- Burn to forget: Teotihuacan ideology through termination rituals at El Rosario, Querétaro / Juan Carlos Saint Charles Zetina and Fiorella Fenoglio Limón -- Teotihuacan and West Mexico: ritual, exchange and interdependence / Agapi Filini -- A multi-scalar view of Los Horcones, Chiapas: intermediate regions and networks of interaction during the Early Classic / Claudia García-Des Lauriers -- A Ojo de Pájaro, A Ojo de Hormiga: perspectives on Teotihuacan and Early Classic interactions in Mesoamerica / Claudia García-Des Lauriers.
Keywords: Indians of Mexico -- Social conditions; Indians of Central America -- Social conditions; Indians of Mexico -- Commerce; Indians of Central America -- Commerce; Indians of Mexico -- Politics and government; Indians of Central America -- Politics and government; Indians of Mexico -- Antiquities; Indians of Central America -- Antiquities; Antiquities, Prehistoric -- Mexico; Antiquities, Prehistoric -- Central America; Social archaeology -- Mexico; Social archaeology -- Central America; Mexico -- Relations -- Central America; Central America -- Relations -- Mexico